El teletrabajo, un indicador de cambio en el mercado de trabajo. - Cámara, Carmen de la (Cuadernos de Relaciones Laborales, 2000)
The new technology of the information and communications era coupled xvith changes in the organisation of labour are leading to a transformation in the way we work. The global economy calís for ihis change and technology enables it. Companies can locate anywhere in the world and organisational structures are becoming flexible. These transformations have clear consequences on labour markets. The new work environment is less stable and more dependent. It is in this context that we frame our interest for tele-communting, a new way of working that is able to adapt to the requirements of flexibility, enabled by new technology. In this article, xve hypothesise that this type of work is developing as outsourcing develops and the labour market becomes more precarious.
Keywords: tele-commuting; labour relations; self-employment; net enterprise; flexibility; organisation of labour; outsourcing; computers